Meningococcal meningitis: clinical and laboratorial characteristics, fatality rate and variables associated with in-hospital mortality - Vanessa L. Strelow; Érique José F. Peixoto de Miranda; Karin R. Kolbe; Juliana V. Souza Framil; Augusto Penalva de Oliveira; José E. Vidal (Arquivos de Neuro-Psiquiatria)
ABSTRACT Meningococcal meningitis is a public health problem. The aim of this study was to describe the clinical characteristics of patients with meningococcal meningitis, and to identify associated factors with mortality. This was a retrospective study, between 2006 and 2011, at a referral center in São Paulo, Brazil. Logistic regression analysis was used to identify factors associated with mortality. We included 316 patients. The median age was 16 years (IQR: 7–27) and 60% were male. The clinical triad: fever, headache and neck stiffness was observed in 89% of the patients. The cerebrospinal triad: pleocytosis, elevated protein levels and low glucose levels was present in 79% of patients. Factors associated with mortality in the multivariate model were age above 50 years, seizures, tachycardia, hypotension and neck stiffness. The classic clinical and laboratory triads of meningococcal meningitis were variable. The fatality rate was low. Age, seizures and shock signs were independently associated with mortality.